Arms control and disarmament agreements : texts and histories of the negotiations. - United States. Arms Control and Disarmament Agency. (Washington, D.C. : United States Arms Control and Disarmament Agency, 1990)
Shipping list no.: 90-538-P. "This is the sixth edition of a publication originally issued in 1972."--p. 1. Geneva protocol, June 17, 1925 -- The Antartic treaty, December 1, 1959 -- "Hot line" agreement, June 20, 1963 -- Limited test ban treaty, August 5, 1963 -- Outer space treaty, January 27, 1967 -- Latin America nuclear-free zone treaty, February 14, 1967 -- Non-proliferation treaty, July 1, 1968 -- Seabed arms control treaty, February 11, 1971 -- "Accidents measures" agreement, September 30, 1971 -- "Hot line" modernization agreement, September 30, 1971 -- Biological weapons convention, April 20, 1972 -- Incidents at sea agreement, May 25, 1972 -- Strategic arms limitations talks (SALT I) -- ABM treaty, May 26, 1972 -- Interim agreement, May 26, 1972 -- Prevention of Nuclear War Agreement, June 23, 1973 -- ABM protocol, July 3, 1974 -- Threshhold test ban treaty, July 3, 1974 -- PNE treaty, May 28, 1976 -- Environmental modification convention, May 18, 1977 -- U.S.-IAEA safeguards agreement, November 18, 1977 -- Strategic arms limitations talks (SALT II) -- Nuclear material convention, March 3, 1980 -- "Hot line" expansion agreement, July 17, 1984 -- Confidence-and security-building measures document, September 19, 1986 -- Nuclear risk reduction centers, September 15, 1987 -- Intermediate-range nuclear forces, December 8, 1987 -- Ballistic missle launch notification agreement, May 31, 1988. Mode of access: Internet.